2019
DOI: 10.1002/path.5250
|View full text |Cite
|
Sign up to set email alerts
|

Multiregion human bladder cancer sequencing reveals tumour evolution, bladder cancer phenotypes and implications for targeted therapy

Abstract: We present an evolutionary analysis of the relative time of genetic events underlying tumorigenesis in human bladder cancers from 10 whole cystectomy specimens using multiregional whole‐exome sequencing. We timed bladder cancer drivers, mutational signatures, ploidy and copy number alterations, provided evidence for kataegis and correlated alterations with tumour areas and histological phenotypes. We found that: (1) heterogeneous tumour areas/phenotypes had distinct driver mutations, (2) papillary‐invasive tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…To our knowledge, no previously published studies on BC have focused on mutations in normal appearing bladder tissue without being restricted to mutations observed in the tumor. Heide et al [36] performed multiregional WES on samples from whole cystectomies and detected mutations in normal samples as well and characterized early disease drivers. However, in this work no driver mutations specific for normal appearing urothelium were reported, though alterations related to mutational signatures S1 and S5 were identified in normal urothelium from one patient.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no previously published studies on BC have focused on mutations in normal appearing bladder tissue without being restricted to mutations observed in the tumor. Heide et al [36] performed multiregional WES on samples from whole cystectomies and detected mutations in normal samples as well and characterized early disease drivers. However, in this work no driver mutations specific for normal appearing urothelium were reported, though alterations related to mutational signatures S1 and S5 were identified in normal urothelium from one patient.…”
Section: Discussionmentioning
confidence: 99%
“…Improved technology has allowed scientists and clinicians to characterize the heterogeneity of tumor at multiple levels. Moreover, multi-region sequencing was performed in many cancer types, including lung [36], breast [37], kidney [38][39][40], rectal [41], colorectal [42], prostate cancers [43], and BC [44], which provides the opportunity to expose the etiologies of treatment failure and drug resistance. At the molecular level, MIBC is a heterogeneous disease that is characterized by genomic instability and a high somatic mutation rate (median, 5.5 per megabase), similar to non-small cell lung cancer and melanoma [45].…”
Section: Heterogeneity In Bcmentioning
confidence: 99%
“…Current strategies for the treatment of MIBC or other cancers are typically relied on the biopsy of a single primary or metastatic site. In some multifocal cancers, such as breast [37], kidney [38], rectal [41], prostate cancers [43], and BC [44], the majority of point mutations detected in different fragments are frequently unique to a single fragment. These findings indicate that gene mutations found in single biopsies will not necessarily be representative of mutations presented in the entire tumor and ITH has substantial obstacle to appropriate selection of precision therapies.…”
Section: Genomic Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…Heide and colleagues performed multiregional whole exome sequencing of ten RC samples [28]. The authors found APOBEC mutational signatures active in CIS; these appeared to be a source of mutations that persisted as the tumor evolved into invasive cancer.…”
Section: Molecular Biology Of Cismentioning
confidence: 99%